Pengaruh Pemberian Terapi Musik Tradisional Bali terhadap Penurunan Intensitas Nyeri pada Ibu Kala I Fase Aktif - Dewi, Ni Nyoman Julianita; Karuniadi, I Gusti Agung Manik; Purnamayanthi, Pande Putu Indah (STIKes Hamzar, 2025)
Labor pain is a physiological process. Most women begin to feel pain during the latent phase of the first stage, and the intensity gradually increases as the process of delivering the fetus progresses. Labor pain in this study was measured using the Numeric Rating Scale (NRS) questionnaire. One method of managing this pain is distraction therapy through the use of traditional Balinese music. The intervention was conducted by providing 30 minutes of traditional Balinese music therapy to women in labor during the active phase of the first stage. This study used a quasi-experimental design with a one-group pretest-posttest design. The sample consisted of 30 women in labor during the active phase of the first stage, selected using non-probability purposive sampling. Data were analyzed using the Wilcoxon test to determine the difference in pain intensity before and after the intervention. The description of pain before the intervention showed that 15 women (50.0%) experienced moderate pain, and 15 women (50.0%) experienced severe pain. After receiving the intervention, 17 women (56.7%) reported mild pain, and 13 women (43.3%) experienced moderate pain. Based on the Wilcoxon test, the p-value was 0.000 < 0.05, indicating that at a 95% confidence level, there was a significant difference in pain intensity before and after traditional Balinese music therapy. Therefore, traditional Balinese music therapy has a significant effect on reducing labor pain. It is recommended that midwives and healthcare providers begin to integrate non-pharmacological approaches in pain management during labor, including the use of traditional Balinese music therapy.